2005
DOI: 10.1128/jvi.79.22.14179-14188.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Can Establish Latent Infection in Resting CD4+T Cells in the Absence of Activating Stimuli

Abstract: Resting CD4؉ T cells are the best-defined reservoir of latent human immunodeficiency virus type 1 (HIV-1) infection, but how the reservoir is formed is unclear. Understanding how the reservoir of latently infected cells forms is critical because it is a major barrier to curing HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
193
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(213 citation statements)
references
References 79 publications
19
193
1
Order By: Relevance
“…Several studies have demonstrated that HIV-1 can establish latency by direct infection of resting CD4 + T cells in vitro (40,67,68). This strategy does have some advantages because it avoids the activation of T cells and utilizes wild-type HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that HIV-1 can establish latency by direct infection of resting CD4 + T cells in vitro (40,67,68). This strategy does have some advantages because it avoids the activation of T cells and utilizes wild-type HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous data (1,38) and those of Vatakis et al (41) suggest that, despite this restriction, HIV can integrate directly into rCD4 cells, although this occurs with slower kinetics and to lower levels in resting cells than in activated cells. Given that dN increase reverse transcription in resting T cells (17), we tested the effect of dN addition on HIV integration and 2LTR formation in resting T cells.…”
Section: Resting Cd4mentioning
confidence: 99%
“…Subsequent studies, using more-sensitive techniques, established that RT in quiescent cells was far slower and less stable than in activated cells (17,36). In addition, we and others demonstrated that while cells activated for 48 h can be efficiently infected, infection prior to T-cell activation is very inefficient, characterized by a large delay in the kinetics of RT and integration, even if the cell is stimulated immediately following infection (11,18,27,30). Therefore, the activation state of T cells markedly affects the progression of the early stages of HIV infection (29).…”
Section: Unlike Activated T Cells Quiescent Cd4mentioning
confidence: 99%